2013
DOI: 10.1093/europace/eut050
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic catheter ablation for induced monomorphic ventricular tachycardia in patients with implantable cardioverter defibrillators as primary prevention

Abstract: Prophylactic CA for induced monomorphic VT reduces the incidence of appropriate ICD therapy including shock in primary prevention patients. These results indicate that prophylactic CA may be considered for structural heart disease patients who are candidates for ICD implantation as primary prevention.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 25 publications
0
8
0
Order By: Relevance
“…In every day practice, NIPS results are also widely used for evaluation of effectiveness of ablative treatment of VT despite limited data from prospective trials. In the future, induction of monomorphic VT at NIPS may be possibly used for identification of patients who could benefit from prophylactic VT ablation; however, our study showed a high negative rather than positive predictive value of NIPS. Nevertheless, future ablative treatment of VT/VF may also consist of more effective, safe, and noninvasive techniques, allowing implementation of VT/VF ablation in more preventive manner.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…In every day practice, NIPS results are also widely used for evaluation of effectiveness of ablative treatment of VT despite limited data from prospective trials. In the future, induction of monomorphic VT at NIPS may be possibly used for identification of patients who could benefit from prophylactic VT ablation; however, our study showed a high negative rather than positive predictive value of NIPS. Nevertheless, future ablative treatment of VT/VF may also consist of more effective, safe, and noninvasive techniques, allowing implementation of VT/VF ablation in more preventive manner.…”
Section: Discussionmentioning
confidence: 58%
“…However, when these therapies occur, ICD interventions can be painful and have negative prognostic value . Modern methods of prevention of ventricular tachycardia (VT) or ventricular fibrillation (VF) in patients with ICD include proper ICD programming, catheter ablation, or treatment with antiarrhythmic drugs . However, prophylactic catheter ablation is rarely performed, whereas antiarrhythmic drugs have limited efficacy and may be harmful.…”
Section: Introductionmentioning
confidence: 99%
“…Second, the risk restratification analysis may be used to identify which patients remain at high risk of VA. This is of particular interest in the ICM cohort where there is growing interest in prophylactic VT ablation . Patient selection for VT ablation remains a controversial area with some centers advocating ablation in all patients receiving an ICD with other centers choosing to ablate only in incessant drug refractory VT.…”
Section: Discussionmentioning
confidence: 99%
“…10 While SMASH-VT showed a significant reduction in ICD shocks in patients who received ICD for secondary prevention, the VTACH trial 10 demonstrated similar benefit from ablation before ICD implantation in patients with tolerated VT. Several single-center retrospective reports strongly suggest that earlier intervention may translate into improved clinical outcomes, highlighting the promising role of upfront ablation. Frankel et al 21 showed that earlier referral for ablation led to an improved 1-year survival free of VT. Hayashi and colleagues 22 in a retrospective study demonstrated improved event-free survival after prophylactic VT ablation in a primary prevention population. Dinov et al 23 demonstrated that early referral for VT ablation was associated with improved acute and long-term freedom from VT recurrence.…”
Section: Current Statementioning
confidence: 97%